Molecular characterization, gene expression and functional analysis of goldfish (Carassius auratus L.) macrophage colony stimulating factor 2 - Gouife, Moussa; Ban, Ziqi; Yue, Xinyuan; Jiang, Jianhu; Xie, Jiasong (Frontiers in Immunology, 2023)
Background Macrophage colony-stimulating factor 2 (MCSF-2) is an important cytokine that controls how cells of the monocyte/macrophage lineage proliferate, differentiate, and survive in vertebrates. Two isoforms of MCSF have been identified in fish, each exhibiting distinct gene organization and expression patterns. In this study, we investigated a goldfish MCSF-2 gene in terms of its immunomodulatory and functional properties. Methods In this study, goldfish were acclimated for 3 weeks and sedated with TMS prior to handling. Two groups of fish were used for infection experiments, and tissues from healthy goldfish were collected for RNA isolation. cDNA synthesis was performed, and primers were designed based on transcriptome database sequences. Analysis of gfMCSF-2 sequences, including nucleotide and amino acid analysis, molecular mass prediction, and signal peptide prediction, was conducted. Real-time quantitative PCR (qPCR) was used to analyze gene expression levels, while goldfish head kidney leukocytes (HKLs) were isolated using standard protocols. The expression of gfMCSF-2 in activated HKLs was investigated, and recombinant goldfish MCSF-2 was expressed and purified. Western blot analysis, cell proliferation assays, and flow cytometric analysis of HKLs were performed. Gene expression analysis of transcription factors and pro-inflammatory cytokines in goldfish head kidney leukocytes exposed to rgMCSF-2 was conducted. Statistical analysis using one-way ANOVA and Dunnett’s post hoc test was applied. Results We performed a comparative analysis of MCSF-1 and MCSF-2 at the protein and nucleotide levels using the Needleman-Wunsch algorithm. The results revealed significant differences between the two sequences, supporting the notion that they represent distinct genes rather than isoforms of the same gene. Sequence alignment demonstrated high sequence identity with MCSF-2 homologs from fish species, particularly C. carpio, which was supported by phylogenetic analysis. Expression analysis in various goldfish tissues demonstrated differential expression levels, with the spleen exhibiting the highest expression. In goldfish head kidney leukocytes, gfMCSF-2 expression was modulated by chemical stimuli and bacterial infection, with upregulation observed in response to lipopolysaccharide (LPS) and live Aeromonas hydrophila. Recombinant gfMCSF-2 (rgMCSF-2) was successfully expressed and purified, showing the ability to stimulate cell proliferation in HKLs. Flow cytometric analysis revealed that rgMCSF-2 induced differentiation of sorted leukocytes at a specific concentration. Moreover, rgMCSF-2 treatment upregulated TNFα and IL-1β mRNA levels and influenced the expression of transcription factors, such as MafB, GATA2, and cMyb, in a time-dependent manner. Conclusion Collectively, by elucidating the effects of rgMCSF-2 on cell proliferation, differentiation, and the modulation of pro-inflammatory cytokines and transcription factors, our findings provided a comprehensive understanding of the potential mechanisms underlying gfMCSF-2-mediated immune regulation. These results contribute to the fundamental knowledge of MCSF-2 in teleosts and establish a foundation for further investigations on the role of gfMCSF-2 in fish immune responses.